2013
DOI: 10.1016/j.lungcan.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of erlotinib in combination with bevacizumab versus chemotherapy plus bevacizumab in the first-line treatment of advanced non-squamous non-small cell lung cancer

Abstract: The TASK study did not show a benefit in terms of PFS for the combination of erlotinib with bevacizumab in unselected first-line advanced non-squamous NSCLC compared with chemotherapy plus bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The TASK trial showed a second-line proportion of 49% after first-line EB [11]. The SAKK (Swiss Group for Clinical Cancer Research) reported on a fixed-sequence protocol with initial EB treatment, showing a higher starting proportion in second-line treatment (62 (61%) out of 101) but a substantial drop down for those receiving four cycles or more (35 (35%) out of 101) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TASK trial showed a second-line proportion of 49% after first-line EB [11]. The SAKK (Swiss Group for Clinical Cancer Research) reported on a fixed-sequence protocol with initial EB treatment, showing a higher starting proportion in second-line treatment (62 (61%) out of 101) but a substantial drop down for those receiving four cycles or more (35 (35%) out of 101) [17].…”
Section: Discussionmentioning
confidence: 99%
“…The DSMB reviewed the study performance at regular intervals. When unfavourable results emerged in the TASK trial (a study of tarceva (erlotinib) in combination with avastin (bevacizumab) in patients with advanced NSCLC) [11], which used similar comparators, the DSMB reviewed current, interim efficacy data from the INNOVATIONS trial and indicated no reason to stop the trial. The study was conducted in accordance with the Declaration of Helsinki (version 1996) and the applicable ICH-GCP (International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use, Good Clinical Practice) guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab in combination with 5-fluorouracilbased chemotherapy has been approved as first/second line therapy for advanced colorectal cancer (CRC) and in combination with carboplatin and/or paclitaxel has been approved as first line therapy for advanced non-small cell lung cancer (NSCLC). [18][19][20][21] The success of bevacizumab can be attributed to its sustained target inhibition resulted from its long half-life and good safety profile due to its high specificity allowing it to combine with a variety of chemotherapies. However, bevacizumab has its limitations in the clinic, such as its intravenous dosing, immunogenicity and potential to induce autoimmune diseases after long term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a double-blind, placebo-controlled, phase 3 trial, this combination regimen significantly prolonged PFS in patients with recurrent or refractory NSCLC compared with the effects of Erl alone (median 3.4 vs 1.7 months; HR=0.62, 95% CI 0.52 to 0.75) 13. However, a contradictory result was obtained in another phase 2 study, in which the combination therapy shortened PFS compared with Bev+CT (BC; 18.4 vs25.0 months; HR=2.05, 95% CI 1.11 to 3.77) 14. The treatment line might affect the efficacy of Bev and Erl.…”
Section: Introductionmentioning
confidence: 99%